2013
DOI: 10.1002/lary.24054
|View full text |Cite
|
Sign up to set email alerts
|

Auditory maturation in premature infants

Abstract: Delayed maturation of an immature auditory pathway might be an important reason for referral after newborn hearing screening in premature infants. Caution is advised regarding early cochlear implantation in preterm born infants. Audiological follow-ups until at least 80 weeks gestational age are therefore recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
0
12
1
6
Order By: Relevance
“…Coenraad et al [13] found significant improvement towards normal hearing or minimal hearing loss in 21.2% of HR infants with symmetric sensorineural hearing loss, including a child whose initial absent ABR recovered completely at follow-up examination. Hof et al [15] reported similar findings in a number of preterm infants with initially abnormal ABR thresholds. Interestingly, 64% of their population showed full or partial recovery on reevaluation within the first year of life.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Coenraad et al [13] found significant improvement towards normal hearing or minimal hearing loss in 21.2% of HR infants with symmetric sensorineural hearing loss, including a child whose initial absent ABR recovered completely at follow-up examination. Hof et al [15] reported similar findings in a number of preterm infants with initially abnormal ABR thresholds. Interestingly, 64% of their population showed full or partial recovery on reevaluation within the first year of life.…”
Section: Discussionmentioning
confidence: 59%
“…Those changes concerned not only the restoration of prolonged latencies after therapy but also the appearance of normal waveforms in cases with completely absent responses [16]. More recently, the widespread application of objective hearing tests for clinical and screening purposes has facilitated the diagnosis of more cases with hearing restoration during infancy [7–15]. The observed improvement of hearing thresholds has been mainly attributed to delayed maturation/myelination of the auditory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Вместе с тем недоношенные дети остаются группой максимального риска нарушений развития и формирования тяжелой соматической и неврологической патологии, что особенно актуально для тех, кто родился глубоко недоношенным -на сроках гестации 31 нед и менее, с массой тела не более 1500 г [2,3]. Так, вероятность возникновения слуховых нарушений у глубоко недоношенных детей в 20-30 раз выше, чем в целом в популяции [2,[4][5][6]. Широко известными факторами риска формирования тугоухости у таких младенцев, помимо глубокой недоношенности, являются хронические заболевания материи, патология беременности, гипоксия в родах, внутриутробное инфицирование, в частности цитомегаловирусом (ЦМВ), наличие коморбидных состояний: врожденных пороков сердца (ВПС), персистенции открытого артериального протока (ОАП), бронхолегочной дисплазии (БЛД), ретинопатии недоношенных, неонатального сепсиса; неонатальная гипербилирубинемия с заменными гемотрансфузиями; приобретенная патология головного мозга (гипоксически-ишемическое поражение (ГИП) центральной нервной системы (ЦНС) с формированием субэпендимальных (СЭК) и внутрижелудочковых (ВЖК) кровоизлияний, перивентрикулярной лейкомаляции (ПВЛ); бактериальные и вирусные менингиты; искусственная вентиляция легких (ИВЛ), а также прием ототоксических препаратов длительностью более 5 сут; длительная шумовая экспозиция в отделениях интенсивной терапии [3,[6][7][8][9][10][11][12].…”
Section: принятые сокращенияunclassified
“…Перцептивная тугоухость при недоношенности носит мультифакториальный характер и может быть обусловлена поражением главным образом наружных волосковых клеток с формированием хронической сенсоневральной тугоухости (ХСНТ); внутренних волосковых клеток, синапсов между ними и спиральным ганглием, а также собственно слухового нерва, что приводит к возникновению слуховой нейропатии (СН) или заболеваний спектра аудиторных нейропатий; проводящих путей и центров слуховой системы, что способствует развитию центральных слуховых расстройств [3,13,14]. Для слуховых нарушений при недоношенности характерны нестабильность слуховых порогов [9,15], возможность улучшения периферической слуховой функции со временем [4,[16][17][18][19] или, напротив, прогрессирующее течение тугоухости, а также отсроченная манифестация последней [9,15,20,21]. Своевременное выявление слуховых расстройств у недоношенных детей и соответственно их ранняя и адекватная реабилитация позволяют оказывать регулирующее воздействие на процессы созревания в центральных отделах слухового анализатора.…”
Section: принятые сокращенияunclassified
See 1 more Smart Citation